Peran Pengadilan Agama Sentani Dalam Menangani Kasus Perceraian Pada Masa Pandemi Covid-19 - Yulia Sulistiyo Rini; Moh Wahib; Laili Shofiya Kurniawati (Institut Agama Islam Negeri Fattahul Muluk Papua, 2022)
The Covid-19 pandemic that is prone to household problems to divorce. The reality is that divorce has an impact on the Sentani Religious Court. Therefore, the researchers raised and answered the problem related to the factors causing divorce and the procedure for handling divorce cases at the Sentani Religious Court during the pandemic, as well the role of the Sentani Religious Court in handling divorce cases during the Covid-19 pandemic. This research uses qualitative methods with this type of field research and a normative juridical approach. Research location in the Sentani Religious Court, with data sourced from primary and secondary data. Researcher processing data by collecting, checking, and compiling data. Next, the researcher analyzes by summarizing and presenting the data in the form of a narrative to conclude. Test the validity of the data by triangulating and use reference materials.The results of this study were the factors causing divorce at the Sentani Religious Court during the Covid-19 pandemic, namely the Covid-19 pandemic that affected the family economy, one party left the house for no reason, the husband gambled and got drunk, domestic violence, and infidelity. The procedures for handling divorce cases during the Covid-19 pandemic are the usual litigation procedures from registration, trial to decisions with health protocols, and electronic litigation procedures (e-Court) from online case registration (e-Filing), online down payments (e-Payment), online summons of parties (e-Summons), and online trial (e-Litigation). The role of Sentani Religious Court in handling divorce during the Covid-19 pandemic is the application of health protocols in the Court environment, the use of electronic litigation applications (e-Court) where there was a lack of understanding of the parties regarding the technology and the occurrence of zero cases in May and December 2020.